Rise of Geopolitics and Changing Korea and Japan Trade Politics - Byung-il Choi; Jennifer S. Oh (East Asian Economic Review (EAER), 2022)
In the past decade, Korea and Japan have increasingly exhibited different strategic priorities in trade in face of China's rising global economic prowess and worsening US-China trade conflict. Japan's trade policy decisions have worked to reinforce its economic and security ties with the US as a means to counter China. Japan has used both bilateral and multilateral means to secure its ties with the US against China. In contrast, Korea's trade policy positions have been one of 'strategic ambiguity'. Korea has been more conciliatory towards China, reluctant to take actions that would counter China's interest. Korea has mainly resorted to bilateral channels to maintain favorable relations with both China and the US. Korea's reluctance to clearly ally with the US against China has been observed across different administrations with opposing political orientations. This paper examines Korea and Japan's diverging strategic priorities in trade through the 2017 World Trade Organization Ministerial Conference; the 2017 US imposition of Section 232 on steel; the Comprehensive and Progressive Agreement for Trans-Pacific Partnership, the Korea-US FTA renegotiation and the Korea-China FTA Phase Two Negotiation; and the 2019 Japan-US Trade Agreement.
Keywords: F50; F51; F53; 330; Korea; Japan; Geopolitics; Trade; Trade Conflict